2022
DOI: 10.1007/978-3-030-87019-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Nigerian COVID-19 Incidence Modeling and Forecasting with Univariate Time Series Model

Abstract: The occurrence of COVID-19 has given rise to dreadful medical difficulties due to its hyper-endemic effects on the human population. This made it fundamental to model and forecast COVID-19 pervasiveness and mortality to control the spread viably.The COVID-19 data used was from February, 28, 2020 to March 1, 2021. ARIMA(1,2,0) was selected for modeling COVID-19 confirmed and ARIMA (1,1,0) for death cases. The model was shown to be adequate for modeling and forecasting Nigerian COVID-19 data based on the ARIMA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the same vein, Anne [4] used a time series model to predict the short-term transmission of the exponentially growing COVID-19 time series, with the aid of simulation. Taiwo et al [5] used the autoregressive integrated moving average (ARIMA) model to model and forecast Nigerian confirmed and death cases as a result of the COVID-19 pandemic. This model predicts the number of cumulative instances over time and is validated using Akaike information criterion (AIC) statistics.…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, Anne [4] used a time series model to predict the short-term transmission of the exponentially growing COVID-19 time series, with the aid of simulation. Taiwo et al [5] used the autoregressive integrated moving average (ARIMA) model to model and forecast Nigerian confirmed and death cases as a result of the COVID-19 pandemic. This model predicts the number of cumulative instances over time and is validated using Akaike information criterion (AIC) statistics.…”
Section: Introductionmentioning
confidence: 99%
“…The human coronavirus was first discovered in 1965, responsible for a significant proportion of upper respiratory tract infections in humans. The study also showed that no fewer than five mutations of new human coronaviruses have been discovered, which has resulted in illness and mortality [1,2]. Severe Acute Respiratory Syndrome (SARS) outbreak started in southern China in 2002-2003 as a form of coronavirus and spread worldwide.…”
Section: Introductionmentioning
confidence: 99%